PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH MADRASAH TSANAWIYAH SWASTA MAMBA’UL ULUM KOTA JAMBI - Ahmad Ridwan; Madyan Madyan; Rian Avinash; Suntari Sukadi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Pedagogic competence is one of the abilities that must be possessed by a teacher in teaching. The pedagogic competencies possessed by teachers at Private Madrasah Tsanawiyah Mamba'ul Ulum are quite good, such as making lesson plans, managing teaching and learning interactions, mastering teaching materials and other elements. However, in ongoing learning the abilities possessed by the teacher are not maximized so that they can affect student learning outcomes. The method used in this research is quantitative. The research hypothesis is that there is an effect of teacher pedagogic competence on student learning outcomes. The sampling technique was taken by using non-probability sampling technique with purposive sampling technique and simple random sampling technique. The population in this study was 50 students, namely class VIII A - VIII B, for the sample in this study were 44 respondents. This study used observation data collection techniques, questionnaires (questionnaire) and documentation. The questionnaire is aimed at students to find data about scores and the influence of teacher pedagogical competence. Documentation that aims to obtain information about learning outcomes, school history and so on. The results of this study concluded that there was an effect of teacher pedagogic competence on student learning outcomes at Private Madrasah Tsanawiyah Mamba'ul Ulum, Paal Merah District, Talang Bakung Village, Jambi City. This is evident from the results of calculating the effect of variable X (teacher's pedagogic competence) on variable Y (student learning outcomes) of 0.365. Based on r_table at the 5% level = 0.297. Thus, it is known that r_xy=0.365> r_table=0.297 at a significance level of 5% so that it can be declared significant. Therefore, it can be concluded that the teacher's pedagogical competence influences student learning outcomes at Private Madrasah Tsanawiyah Mamba'ul Ulum Jambi City.